2015
DOI: 10.1371/journal.pone.0120151
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reconstruction through Poisson Disk Sampling

Abstract: This paper intends to generate the approximate Voronoi diagram in the geodesic metric for some unbiased samples selected from original points. The mesh model of seeds is then constructed on basis of the Voronoi diagram. Rather than constructing the Voronoi diagram for all original points, the proposed strategy is to run around the obstacle that the geodesic distances among neighboring points are sensitive to nearest neighbor definition. It is obvious that the reconstructed model is the level of detail of origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Convergence issues emerged in some cases involving highly strained areas, especially in the intervertebral disks, and were arguably related to the local mesh quality. However, the approach used for the geometrical generation of the intervertebral disks provides a smooth, high quality surface mesh, which constitutes an appropriate input for volume meshing (Hou et al, 2015 ). Nevertheless, local mesh refinement may improve convergence in selected cases, and should be taken into account as a possible future development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Convergence issues emerged in some cases involving highly strained areas, especially in the intervertebral disks, and were arguably related to the local mesh quality. However, the approach used for the geometrical generation of the intervertebral disks provides a smooth, high quality surface mesh, which constitutes an appropriate input for volume meshing (Hou et al, 2015 ). Nevertheless, local mesh refinement may improve convergence in selected cases, and should be taken into account as a possible future development.…”
Section: Discussionmentioning
confidence: 99%
“…First, the surface nodes belonging to the endplate regions of the vertebrae are identified as described above. Then, the convex hull of the selected nodes is computed and resampled by means of the Poisson surface reconstruction algorithm (Hou et al, 2015 ) implemented in Meshlab. The elements belonging to a cylindrical region around the craniocaudal axis, the diameter of which is automatically calculated so that its volume is the 50% of that of the whole disk (Iatridis et al, 1996 ), are then identified as the nucleus pulposus (Figure 4 ), whereas the remaining elements constitute the annulus fibrosus.…”
Section: Methodsmentioning
confidence: 99%